Maintained physical activity and physiotherapy in the management of distal arm pain: a randomised controlled trial. Issue 1 (4th March 2019) - Jones, Gareth T; Macfarlane, Gary J; Walker-Bone, Karen; Burton, Kim; Heine, Peter; McCabe, Candida; McNamee, Paul; McConnachie, Alex; Zhang, Rachel; Whibley, Daniel; Palmer, Keith; Coggon, David
Abstract : Objectives: The epidemiology of distal arm pain and back pain are similar. However, management differs considerably: for back pain, rest is discouraged, whereas patients with distal arm pain are commonly advised to rest and referred to physiotherapy. We hypothesised that remaining active would reduce long-term disability and that fast-track physiotherapy would be superior to physiotherapy after time on a waiting list. Methods: Adults referred to community-based physiotherapy with distal arm pain were randomised to: advice to remain active while awaiting physiotherapy (typically delivered after 6–8 weeks); advice to rest while awaiting physiotherapy, or immediate treatment. Intention-to-treat analysis determined whether the probability of recovery at 26 weeks was greater among the active advice group, compared with those advised to rest and/or among those receiving immediate versus usually timed physiotherapy. Results: 538 of 1663 patients invited between February 2012 and February 2014 were randomised (active=178; rest=182; immediate physiotherapy=178). 81% provided primary outcome data, and complete recovery was reported by 60 (44%), 46 (32%) and 53 (35%). Those advised to rest experienced a lower probability of recovery (OR: 0.54; 95% CI 0.32 to 0.90) versus advice to remain active. However, there was no benefit of immediate physiotherapy (0.64; 95% CI 0.39 to 1.07). Conclusions: Among patients awaiting physiotherapy for distal arm pain, advice to remain active results in better 26-week functional outcome, compared with advice to rest. Also, immediate physiotherapy confers no additional benefit in terms of disability, compared with physiotherapy delivered after 6–8 weeks waiting time. These findings question current guidance for the management of distal arm pain.